Response Time Inconsistencies in Object and Action Naming in Anomic Aphasia - Galletta, Elizabeth E. (Am J Speech Lang Pathol, 2018)
PURPOSE: The effect of repeated naming on both object and action picture naming in individuals with anomic aphasia is explored. We asked whether repeatedly naming the same items leads to improved accuracy and reduced response latency. METHOD: Ten individuals with anomic aphasia and 6 healthy adults, 3 young and 3 old, named a set of 27 object pictures and a set of 27 action pictures presented 1 at a time on a computer screen. We examined accuracy and response times (RTs) across the 2 blocks of 10 repeated trials. RESULTS: Results demonstrated higher accuracy and faster RTs for object than for action naming for all participants, with lower accuracy rates and slower RTs for the people with aphasia (PWA) compared with the healthy individuals, and diverging patterns of change across trials. Unlike the healthy participants, whose RTs decreased across trials, PWA continued to demonstrate variability in response latencies across the trials. CONCLUSIONS: Our preliminary results suggest that measuring RT may be useful in characterizing retrieval difficulty in anomic aphasia and that the retrieval processes in PWA, even in those who experience mild anomia, may be less efficient or different from those processes in neurologically healthy individuals.